2019
DOI: 10.1080/17461391.2019.1584249
|View full text |Cite
|
Sign up to set email alerts
|

Sport experience is correlated with complex motor skill recovery in youth following concussion

Abstract: A previous study showed prolonged cognitive-motor integration (CMI) deficits in youth with a history of concussion who were classified as asymptomatic by current return-to-play protocols, highlighting potential differences between clinical symptom recovery and skill recovery. The present study examines factors that may influence skilled performance recovery (defined as matching the skill level of no-concussion history peers) post-concussion in a similar cohort. Sixty-four asymptomatic youth (M = 13 yrs.) socce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 42 publications
5
28
0
Order By: Relevance
“…The present findings combined with previous discoveries [8] may partially explain why youth who returned to game-play after a concussion are at a higher risk of incurring another concussion or injury within the first year post-injury [11,12]. In previous studies, it was shown that lingering eye-hand decoupling deficits remained present for much longer than previously expected in both asymptomatic youth [8,9] and asymptomatic elite athletes [14] who had all returned to play. In the present study, we expand on these findings with details about the time course of EHD deficits in youth with concussion history to include task demand.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The present findings combined with previous discoveries [8] may partially explain why youth who returned to game-play after a concussion are at a higher risk of incurring another concussion or injury within the first year post-injury [11,12]. In previous studies, it was shown that lingering eye-hand decoupling deficits remained present for much longer than previously expected in both asymptomatic youth [8,9] and asymptomatic elite athletes [14] who had all returned to play. In the present study, we expand on these findings with details about the time course of EHD deficits in youth with concussion history to include task demand.…”
Section: Discussionsupporting
confidence: 75%
“…In line with these findings, previous work has shown prolonged eye-hand coordination deficits in youth with concussion history for up to 1.5 years post-concussion when participant's performed a challenging cognitive-motor task that required a decoupling of eye and hand movement direction [8,9]. Importantly, all of the young athletes involved in these studies had already returned to game play after their concussion, in accordance with the current return to play protocols at the time the concussion-incident occurred [10].…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…We have used our task in several sport concussion studies (29)(30)(31)(32), and always observe significant differences in performance outcomes related to both timing and accuracy in concussed athletes vs. controls. We compared youth athletes (8-16 years old) with a history of concussion who were asymptomatic and deemed recovered (33) to age-matched controls with no history of concussion (30).…”
Section: A Failure To Communicate: the Effect Of Mild Brain Injury Onmentioning
confidence: 99%